National Prosecutors Survey (Census), 2007 ([Verlag nicht ermittelbar], 2012)
The 2007 Census of State Court Prosecutors marked the second BJS survey of all prosecutors' offices in the United States. The first census, conducted in 2001, included the 2,341 offices in operation at that time. The second census included the 2,330 state court prosecutors' offices operating in 2007. Neither census included offices of municipal attorneys or county attorneys, who primarily operate in courts of limited jurisdiction. State court prosecutors serve in the executive branch of state governments and handle felony cases in state courts of general jurisdiction. By law, these prosecutors are afforded broad discretion in determining who is charged with an offense and whether a case goes to trial. The chief prosecutor, also referred to as the district attorney, county attorney, commonwealth attorney, or state's attorney, represents the state in criminal cases and is answerable to the public as an elected or appointed public official. The Office of the United States Attorney for the District of Columbia is the only federal prosecutor included in the census. This unique office is responsible for prosecution of serious local crimes committed in the District and also for prosecution of federal cases, whether criminal or civil.